2010
DOI: 10.1080/08870440903055893
|View full text |Cite
|
Sign up to set email alerts
|

The role of attitudes towards the targets of behaviour in predicting and informing prenatal testing choices

Abstract: Research considering the role of attitudes in prenatal testing choices has commonly focused on the relationship between the attitude towards undergoing testing and actual testing behaviour. In contrast, this study focused on the relationship between testing behaviour and attitudes towards the targets of the behaviour (in this case people with Down syndrome (DS) and having a baby with DS). A cross-sectional, prospective survey of 197 pregnant women measured attitudes towards the targets of prenatal testing alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Those who used screening and (hypothetically) intended to use amniocentesis and termination held less-positive attitudes towards the condition than did those who did not use/did not intend to use them. However, while attitudes towards people with DS were good predictors of intentions to terminate for the condition, they were only weak predictors of screening behaviour (Bryant et al, 2010). Qualitative data revealed that women did not consider their attitudes towards DS as salient to their screening decision, only to decisions about diagnostic testing or termination; it is also possible that attitudinal ambivalence may have been partly responsible for the weak relationship.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Those who used screening and (hypothetically) intended to use amniocentesis and termination held less-positive attitudes towards the condition than did those who did not use/did not intend to use them. However, while attitudes towards people with DS were good predictors of intentions to terminate for the condition, they were only weak predictors of screening behaviour (Bryant et al, 2010). Qualitative data revealed that women did not consider their attitudes towards DS as salient to their screening decision, only to decisions about diagnostic testing or termination; it is also possible that attitudinal ambivalence may have been partly responsible for the weak relationship.…”
Section: Introductionmentioning
confidence: 70%
“…In this study, a higher level of ambivalent beliefs about parenting a child with DS was associated with having a screening test, but this was the only significant relationship identified in the screening analyses. It may be that attitudes towards DS do not always play a significant role in screening decisions because they are not always seen as relevant at this stage in the testing process (Bryant et al, 2010). The relationship between ambivalence to DS and amniocentesis intention was stronger although it is likely that concern about miscarriage is also an important factor in uncertainty in this respect (Sapp et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One problem with this approach is that any list of categories may not sufficiently account for the variable expression of many disorders. A further concern is that the severity of different diseases is perceived differently between and among professionals [Wertz and Knoppers, 2002] and pregnant women [Bryant et al, 2010]. As indicated, the practical feasibility of such alternative models of informed consent needs to be tested in empirical studies.…”
Section: Meaningful Informed Consent For Prenatal Testingmentioning
confidence: 99%